Enhancing the mechanical properties of BN nanosheet-polymer composites by uniaxial drawing - KHAN, UMAR; MAY, PETER; COLEMAN, JONATHAN (My University, 2014)
We have used liquid exfoliation of hexagonal Boron-Nitride (BN) to prepare composites of BN nanosheets of three different sizes in polyvinylchloride matrices. These composites show low levels of reinforcement, consistent with poor alignment of the nanosheets as-described by a modified version of Halpin-Tsai theory. However, drawing of the composites to 300% strain results in a considerable increase in mechanical properties with the maximum composite modulus and strength both ∼×3 higher than that of the pristine polymer. In addition, the rate of increase of modulus with BN volume fraction was up to 3-fold larger than for the unstrained composites. This is higher than can be explained by drawing-induced alignment using Halpin-Tsai theory. However, the data was consistent with a combination of alignment and strain-induced de-aggregation of BN multilayers.
PUBLISHED
Keywords: Nanoscience